Determinantes emergentes da produtividade em Tribunais de Justiça estaduais - Sátiro, Renato Máximo (2019)
Much has been discussed about the factors that would lead to an efficient or inefficient performance of the Brazilian Judiciary, and a part of the academic discussions regarding the field of Administration of Justice, concerns the performance/productivity antecedents related to the courts and magistrates. In this sense, the main objective of the present work was to discuss the determinant aspects of the productivity of the State Courts of Justice in Brazil and to test emerging variables that may help in this understanding. From an analysis of the literature, we selected the variables already consolidated: workload, human resources (effective servers and outsourced employees), investment in ICT; and the emerging variables: lawyers and conciliators. Data from the Justice in Numbers (Justiça em Números) Report and from the Brazilian Federal Council of the Bar Association OAB from the 2011 to 2017 years of the 27 Brazilian Courts of Justice were collected from a total of 189 observations. The inference technique used was the Multiple Regression with panel data. After the test and validation of the Regression model and assumptions, the hypothesis that the number of lawyers, the workload and the amount effective servers and outsourced employees affects the productivity of the courts is confirmed; on the other hand, it was concluded that investment in technology did not influence the productivity of the State Courts of Justice. Finally, the results point in the opposite direction of the CNJ guidelines; it was concluded that the number of conciliators is not related to the productivity of the Courts of Justice.